The Influence of Social Comparison and Self-Concept on Social Anxiety in Early Level Students of The Faculty of Psychology X Who Use Social Media Instagram - Sulthon, Mohammad; Sovitriana, Rilla (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
This study aims to examine the effect of social comparison and self-concept on social anxiety in early-level students of the Faculty of Psychology UPI Y.A.I who use Instagram social media. Social media is a place to interact with other people and as a means that can be used to express oneself, personal information and vent one's emotions through the internet or social media. The population in this study were undergraduate students of class 2022/2023, 2023/2024 with a total of 189 people. The sampling technique used in this study was purposive sampling. Data collection methods using the Iowa-Netherlands Comparison Orientation Measure (INCOM) social comparison scale, self-concept scale and Social Anxiety Scale for Social Media Users (SAS-SMU) with a Likert scale model. The research results were processed using the JASP version 00.19.00.0 application for Windows. Based on the results of partial hypothesis testing, it shows that there is an influence with a negative direction between social comparison on the social anxiety of students who use Instagram social media, the results of partial hypothesis testing show that there is an influence with a positive direction between self-concept on student social anxiety. The results of simultaneous hypothesis testing show that there is a significant influence between social comparison and self-concept on social anxiety in early level students of the Faculty of Psychology UPI Y.A.I.